P118 Predicting survival in patients admitted to hospital with an acute exacerbation of Chronic Obstructive Pulmonary Disease (COPD). (16th November 2010) - Williamson, K; Sullivan, A; Folland, N; Rees, S; Gompertz, S
Abstract : Introduction: COPD is the fifth biggest cause of death in the UK. It can be difficult to predict when these patients are coming to the end of their life. There are many clinical tools available to aid prediction of death.1 2 As part of a wider COPD audit we assessed whether one of these could identify which patients admitted with an exacerbation should be referred for specialist palliative care. Method: 50 consecutive patients admitted to an acute hospital with exacerbations of COPD were assessed between August and September 2009. Gold Standards Framework1 indicators for organ disease and other general predictors of end-stage illness were recorded. Where available (33/50), we calculated a modified BODE score (without the measure of exercise capacity). At 10 months, we assessed how many patients had survived. Results: 30% (15/50) of the patients had died by 10 months. Median BOD score at admission was five in survivors and in those who had died. The remaining data are summarised in Abstract P118 Table 1 . Discussion: In our group of patients a modified BODE score was not helpful in predicting outcome at 10 months. Recurrent admissions, oxygen therapy, severe breathlessness/dependence and resistant organisms were more prevalent in the group that died. These data are being used in further developments to care pathways within our Trust.